Androgen deficiency in postmenopausal - Pacheco Romero, José (2015)
Menopause is characterized by a series of modifications of the female body caused by modulation in the production of estrogens and androgens. We review the knowledge on variations of these steroids, mainly androgens, in the post menopausal woman. We try to establish the importance of prohormone testosterone and other androgens deficit, the related clinical consequences and the possibility to revert them by specific measures.